The modern view on optimal therapy of HPV-associated pathology of cervix at the vaginal dysbiosis background - О. А. Таран; О. В. Булавенко; Д. Г. Коньков; Т. В. Лобастова (Publishing House TRILIST, 2018)
Human papillomavirus (HPV) is a proven cause of precancer and cervical cancer. Violation of the vaginal microbiota in women with HPV-associated cervical pathology may contribute to the development of carcinogenesis. Deficiency of lactobacillus contributes to the growth and development of opportunistic microorganisms, reducing the synthesis of bactericidal and antifungal substances. The study of the clinical efficacy of the vaginal Lactoginal® (strain Lactobacillus rhamnosus LCR35), in the complex treatment of HPV-associated cervical pathology at the vaginal dysbiosis background's. The results of the study showed a significant decrease in cases of vaginal dysbiosis, an increase in the number of lactobacilli in the vaginal secretion, a decrease in the microbial associations of relative pathogenic flora, an improvement in local immunity and complete elimination of HPV with the addition of the Lactoginal® to the basic therapy. The results obtained allow us to recommend the Lactoginal® for treatment of precancerous diseases of the cervix.